Konseling Pancawaskita untuk Meningkatkan Keterampilan Praksis Konseling pada Guru BK SMP Negeri 35 Banjarmasin - Ainun Heiriyah; Sri Ayatina Hayati; Farial Farial; Mahfuz Mahfuz (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2020)
The description of the knowledge of the BK teacher of SMP Negeri 35 Banjarmasin shows a low category with an average total score of 9, this shows the provision of this service is very necessary. Meanwhile, the description of BK teacher skills at SMP Negeri 35 Banjarmasin shows a high category with an average total score of 32.5. This shows that the increase in BK teacher skills increased significantly to the Pancawaskita counseling approach. This seems reasonable, because the teacher of BK Negeri 35 Banjarmasin Middle School has been given about the material and training "Pancawakita counseling approach". Keywords: Pancawaskita Counseling, Praxis Counseling Skills